Fernando Cruz Kronfly and the fractured time of Destierro - Simón Henao-Jaramillo (Estudios de Teoría Literaria, 2015)
This paper studies Fernando Cruz Kronfly´s novel Destierro (2012) through categories like anachronism, presenteism and memory (Didi-Huberman, Hartog, Benjamin, among others) in order to investigate the particular way in which the novel temporalizes the experience of exile. Destierro part from a present that, in perpetual motion, leading to a present of the already-gone, a narrative temporality made by absences. The time in this temporality and its links generated produces what we called ghost community, a kind of community which govern relations between that remains present and what does not.